Anticonvulsant effects of Cuminium cyminum L. seeds extracts and essential oil in mice - H Hosseinzadeh; M Ramezani; M Fadishei; M Basirat (Institue of Medicinal Plants, ACECR, 2002)
The anticonvulsant effects of aqueous and ethanolic extracts as well as essential oil of Cuminum cyminum L. seeds were studied in mice. In pentylenetetrazole test, the essential oil and the extracts of seeds prolonged the onset time of tonic convulsion, but failed to produce complete protection against mortality. In this test, the anticonvulsant efficacy of the aqueous (2.8 g/kg) and ethanolic (5 g/kg) extracts was similar as phenobarbital at a dose of 20 mg/kg. In maximal electroshock test, the aqueous (4 g/kg) and ethanolic (5 g/kg) extracts as well as essential oil (0.35 g/kg) decreased the duration of tonic seizures by 37.6%, 68.2% and 59.1%, respectively. These results indicate that the extracts and essential oil of Cuminum cyminum seeds may have efficacy in petit mal and grand mal seizures.